The Influence Of Organizational Culture And Work Motivation On Employee Performance at PT. PLN (Persero) Main Unit, East Nusa Tenggara Region - Jehalut, Marianus Rivanto; Gana, Frans; Maku, Grace Martiani (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to explain how PT. PLN (Persero) UIW NTT employees perceive organizational culture, work motivation, and performance; determine whether organizational culture influences PT. PLN (Persero) UIW NTT employees' performance; determine whether work motivation influences PT. PLN (Persero) UIW NTT employees' performance; and explain the simultaneous influence of organizational culture and work motivation on performance. This study, which uses 89 PT. PLN (Persero) UIW NTT employees as samples, is categorized as quantitative. This study employed observation, questionnaires, interviews, and documentation as data gathering methods. Data analysis used descriptive analysis approaches, multiple linear statistical analysis, and hypothesis testing. The study's findings demonstrate that PT. PLN (Persero) UIW NTT employees' performance is significantly and favorably impacted by the organizational culture variable. In the meantime, PT. PLN (Persero) UIW NTT employees' performance was determined to be positively and significantly impacted by the partial test of work motivation. PT. PLN (Persero) UIW NTT employees' performance is positive and significantly impacted by the variables of work motivation and culture concurrently.